Answer:
The horizontal shift depends on the value of h h. The horizontal shift is described as: g(x) = f (x+h) g ( x) = f ( x + h) - The graph is shifted to the left h h units. g(x) = f (x−h) g ( x) = f ( x - h) - The graph is shifted to the right h h units. The vertical shift depends on the value of k k.
Step-by-step explanation:
Half of 57 is 28.5. Hoped I helped. :)
Answer:
- 43
Step-by-step explanation:
Expression: (3m+2n−6) and (−4−6m+7n)
n= -2 and m=5
Before inserting the values, let's add both expressions.
(3m+2n−6) + (−4−6m+7n)
3m+2n−6 −4 − 6m + 7n
-3m + 9n - 10
Inserting the values;
-3(5) + 9(-2) - 10
-15 - 18 -10
- 43
The x-intercept of f(x) = (x + 6)(x - 3)
f(x) = 0 → (x + 6)(x - 3) = 0 → x + 6 =0 or x - 3 =0
x = -6 or x = 3
Therefore the x-intercepts are: (-6; 0) and (3; 0)
Your answer is (-6; 0)